Challenges of a New Investment Policy: Investment Promotion and Protection - E. V. Sapir; I. A. Karachev (Финансы: теория и практика, 2020)
The study aims to analyze key aspects of the new emerging investment policy, which sets the priority for private investment protection and promotion. The relevance of the study is due to the search for new, nonbudget, funding sources for implementing large-scale national tasks and large infrastructure projects. Attracting private capital within changing global investment becomes an important task for national governments, and therefore requires a departure from investment protectionism to investment protection and promotion. Due to the methods of theoretical (analysis, synthesis, generalization, historical method) and empirical (comparison, measurement) research, the authors managed to reveal the main economic determinants and components of the national investment climate that contribute to attracting foreign capital; to systematize the key measures of investment policy; to identify trends in the dynamics of global flows of foreign direct investment. As a result, the authors established key principles and criteria for the new investment policy of sustainable development, as well as identified contemporary models of the new investment policy. These include a model for stimulating the development of individual priority economic activities; a model for improving the technological level of national industries; a model for creating new integrated meta-industries. The authors focus on reforming the investment regime in the Russian Federation. The new legislation provides for the possibility to conclude an investment protection and promotion agreement with private investors based on “a stabilization clause”. Thus, investors implementing large-scale investment projects will be subject to new rules that will establish the conditions at the time of the agreement, in particular, tax and customs policies. According to the authors, such agreements will improve the quality of the investment climate in the Russian Federation.